Diagnóstico sobre as práticas de autoconstrução na região metropolitana de Aracaju/SE - Viana, Marina Ribeiro (2021)
Housing self-construction uses the residents as agents for the planning, management, and execution of their homes. In general, this construction regime is not monitored by specialized professionals. Although such a mode of production is a common feature in the Brazilian housing scenario, self-construction is generally associated with the low-income population. This is because access to the formal housing market is not democratic. Thus, the population that does not have enough income finds alternatives in the autonomous production of their residences in places far from the urban center and / or in irregular lots. In this sense, the present work consisted of making a diagnosis about the practices of self-construction in the metropolitan region of Aracaju / SE. Thus, sought to understand the phenomenon of selfconstruction from the perspective of three of its agents: self-builders, Technical Assistance for Social Interest Housing (ATHIS) professionals and public authorities. To this end, an exploratory-descriptive study with a qualitative and quantitative approach was developed, in which questionnaires, interviews with specific audiences and photographic records were used as research tools. As a result, an overview of the self-construction was traced based on the profile of the residents, on the conditions of implementation of the lot, on the peculiarities of the execution process and on the construction techniques used. Still, it was noticed that there is no active role of the public authorities in this type of housing, since its action is mostly supervisory, in the sense of just following the growth of the city and the emergence of precarious settlements. In this way, existing public housing policies are based on the removal and relocation of the family in line with the housing programs launched by the Federal Government, but there is no formal ATHIS program or incentive for assisted selfconstruction. When analyzing the work developed by ATHIS professionals, this lack of incentive or assistance on the part of public entities was reinforced, since the financing of the activities was through the resources of the residents or through an announcement from the Sergipe Architecture and Urbanism Council (CAU / SE). Also, it was identified that the inefficiency of public action, the lack of interested technical professionals and bureaucracy were the main difficulties for the implementation of ATHIS in the municipalities. With this, it is concluded that self-construction in the metropolitan region of Aracaju/SE can be characterized by the evolution and autonomy of the residents, since it is often consolidated through repeated interruptions and with no prospect of completion, it is still shaped by the from the initiative and work of the residents themselves, with the help of family members or hired professionals, generally without the guidance of a technical person and under the omission of the government. Finally, it is expected that the survey on self-construction practices and the actors involved in them, as a result, this work can contribute to stimulating discussions on the subject and the proposition of public policies that address the demands and specificities of self-builders.